The trumpet of the swan - White, E. B.; Frascino, Edward (New York : Harper & Row, 1970)
Knowing how to read and write is not enough for Louis, a voiceless Trumpeter Swan; his determination to learn to play a stolen trumpet takes him far from his wilderness home.
Keywords: Trumpeter swan; Swans